Race riots : comedy and ethnicity in modern British fiction - Ross, Michael L., 1936- (Montreal [Que.] : McGill-Queen's University Press, 2006)
Ross examines racial humour as a manifestation of post-colonialism and questions contemporary critiques of "political correctness." Looking at cartoons from pre-World War II issues of Punch, Ross shows how disdain for non-Europeans plays a key role in period British humour and links this idea to the racial humour in the work of Evelyn Waugh and Joyce Cary. He also demonstrates how these assumptions are later turned on their heads by writers such as Salman Rushdie.
Caliban and his progeny -- Inferiority complexions: the London charivari -- White mischief: Evelyn Waugh's African charivari -- Joyce Cary's tragic African clown -- Forster's funny bridge party: nation and humour in A passage to India -- Roman Catholic carnival: Muriel Spark's passage to Jerusalem -- The far and the near: Pym and Taylor -- Samuel Selvon and the carnival of reverse colonization -- Rerouting the comic: Salman Rushdie's The satanic verses -- "A funny kind of Englishman": Hanif Kureishi's carnival of ethnicities -- "Some subtleties of the isle": Matthew Kneale's anti-Tempest -- The empire laughs last.
Includes bibliographical references (pages 291-302) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
In English.
Keywords: English fiction -- History and criticism; Laughter in literature; Comic, The, in literature; Stereotypes (Social psychology) in literature; Racism in literature; Racisme dans la littérature.; Stéréotypes dans la littérature.; Comique dans la littérature.; Rire dans la littérature.; Roman anglais -- Histoire et critique; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Comic, The, in literature; English fiction; Laughter in literature; Racism in literature; Stereotypes (Social psychology) in literature; Electronic books; Criticism, interpretation, etc